Green synthesis of gold nanoparticles using plant extracts as reducing agents - Elia P (Dove Medical Press, 2014)
Paz Elia,1 Raya Zach,1 Sharon Hazan,2 Sofiya Kolusheva,2 Ze’ev Porat,1,3 Yehuda Zeiri1,3 1Department of Biomedical Engineering, 2Ilse Katz Institute of Nanotechnology, Ben-Gurion University of the Negev, 3Division of Chemistry, Negev Nuclear Research Center Beersheba, Israel Abstract: Gold nanoparticles (GNPs) were prepared using four different plant extracts as reducing and stabilizing agents. The extracts were obtained from the following plants: Salvia officinalis, Lippia citriodora, Pelargonium graveolens and Punica granatum. The size distributions of the GNPs were measured using three different methods: dynamic light scattering, nanoparticle-tracking analysis and analysis of scanning electron microscopy images. The three methods yielded similar size distributions. Biocompatibility was examined by correlation of L-cell growth in the presence of different amounts of GNPs. All GNPs showed good biocompatibility and good stability for over 3 weeks. Therefore, they can be used for imaging and drug-delivery applications in the human body. High-resolution transmission electron microscopy was used to view the shapes of the larger GNPs, while infrared spectroscopy was employed to characterize the various functional groups in the organic layer that stabilize the particles. Finally, active ingredients in the plant extract that might be involved in the formation of GNPs are proposed, based on experiments with pure antioxidants that are known to exist in that plant. Keywords: gold nanoparticles, Lippia citriodora, Salvia officinalis, Pelargonium graveolens, Punica granatum, antioxidants, size distribution, zeta potential